Development of a fluorescent based immunosensor for the serodiagnosis of canine leishmaniasis combining immunomagnetic separation and flow cytometry. - Susana Sousa; Luís Cardoso; Steven G Reed; Alexandre B Reis; Olindo A Martins-Filho; Ricardo Silvestre; Anabela Cordeiro da Silva (Public Library of Science (PLoS), 2013)
BACKGROUND: An accurate diagnosis is essential for the control of infectious diseases. In the search for effective and efficient tests, biosensors have increasingly been exploited for the development of new and highly sensitive diagnostic methods. Here, we describe a new fluorescent based immunosensor comprising magnetic polymer microspheres coated with recombinant antigens to improve the detection of specific antibodies generated during an infectious disease. As a challenging model, we used canine leishmaniasis due to the unsatisfactory sensitivity associated with the detection of infection in asymptomatic animals where the levels of pathogen-specific antibodies are scarce. METHODOLOGY: Ni-NTA magnetic microspheres with 1,7 µm and 8,07 µm were coated with the Leishmania recombinant proteins LicTXNPx and rK39, respectively. A mixture of equal proportions of both recombinant protein-coated microspheres was used to recognize and specifically bind anti-rK39 and anti-LicTNXPx antibodies present in serum samples of infected dogs. The microspheres were recovered by magnetic separation and the percentage of fluorescent positive microspheres was quantified by flow cytometry. PRINCIPAL FINDINGS: A clinical evaluation carried out with 129 dog serum samples using the antigen combination demonstrated a sensitivity of 98,8% with a specificity of 94,4%. rK39 antigen alone demonstrated a higher sensitivity for symptomatic dogs (96,9%), while LicTXNPx antigen showed a higher sensitivity for asymptomatic (94,4%). CONCLUSIONS: Overall, our results demonstrated the potential of a magnetic microsphere associated flow cytometry methodology as a viable tool for highly sensitive laboratorial serodiagnosis of both clinical and subclinical forms of canine leishmaniasis.